POLA HUBUNGAN KERJASAMA PETANI KARET DENGAN TAUKE (PATRON-CLIENT) DI DESA MUARA MUSU KECAMATAN RAMBAH HILIR KABUPATEN ROKAN HULU - Gunawan, Ikhsan; Bahar, Edward (E-Journal Sungkai, 2012)
The purposes of this research are : to describe the relationshipâs pattern between therubber farmers and the local employer, to know the dependency level of rubber farmers and localemployer, and the problems among this relationshipâs pattern. This research was held in DesaMuara Musu Kecamatan Rambah Hilir Kabupaten Rokan Hulu by using study case method. Theresamples of rubber farmers and 2 local employers. The data analysis was descriptive which waspresented in qualitative analiysis. The research findings show that the relationshipâs patternbetween the rubber farmers and the local employer are a production pattern or trade relation, sosialrelation, debit and credit relation, and overlaping relation. The patron-clientâs relationship of therubber farmers of Desa Muara Musu is Cluster Patront-Client. There are three aspects ofdependency level of rubber farmers and local employer. They are market and productionâsequipment dependence (70 percent), modal dependence (10 parcent), and market-only dependence(20 parcent). All the farmers samples said that they had debt to the local employer, it is about Rp.50.000,- to Rp. 250.000,- , so the local employer will continuously get rubbersâ supply from thefarmers as long as they have not paid it yet. The data also shows that most of the farmers intend tolend some mony from the local employer rather than from a cooperative (100 parcent).